Improvement of vibration and acoustic properties of woven jute/polyester composites by surface modification of fibers with various chemicals - S. Senthilrajan; N. Venkateshwaran; S. O. Ismail; Rajini Nagarajan; Nadir Ayrilmis; Kumar Krishnan; Faruq Mohammad; Hamad A. Al-Lohedan (Scientific Reports, 2025)
Abstract In response to the growing demand for lightweight and sustainable materials, the integration of natural fibers into polymer matrix composites has become very important. To improve the compatibility between hydrophilic natural fibers and matrices, surface modification has proven to be a crucial step. Therefore, this study advanced this technique by modifying the surfaces of woven jute mats with 1% of sodium hydroxide (NaOH), chromium sulphate (Cr2SO4), and sodium bicarbonate (NaHCO3). The composite, containing 56% by volume of the fibers, was produced by compression moulding. Extensive testing was carried out, including three-point bending, free vibration mode and acoustic analysis. The Brüel and Kjær two-microphone impedance tube with a frequency range of 25–6400 Hz was used. Various properties such as bending strength, vibration behaviour, damping and sound absorption were evaluated. It was comparatively evident that the NaHCO3-treated composite samples exhibited the highest natural frequency of 61.04 Hz and the highest sound absorption coefficient of 0.67 at about 2000 Hz, which was 69% higher than that of the untreated composite samples and about 29–72% higher than that of other treated counterparts. In addition, other test results of the surface modified composites were better than the untreated counterparts. There was good agreement between the experimental data and the results obtained from the theoretical models, which is another significant contribution to the field of composite technology.